Dari Idealisme ke Pragmatisme: Pergeseran Paradigma dalam Pengembangan Hukum Ekonomi Syariah di Indonesia - Addiarrahman Addiarrahman; Illy Yanti (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This study seeks to understand the pragmatism of the development of sharia economic law, and its implications for Islamic financial products in Indonesia. The data comes from the results of interviews and focus group discussions with key informants from academics, practitioners, authorities, and the public. This research finds that pragmatism in the development of Islamic economic law is an approach that still dominates the DSN-MUI fatwas. The pragmatism style used is complex-eclectic pragmatism which is represented through makhÄrij al-fiqhiyyah, which is to choose a mild opinion by sticking to the strongest method or also called "taysÄ«r al-manhajÄ«". The use of this method is intended to ensure that the fatwa is truly able to answer the needs of the business world, as well as being in line with sharia principles. DSN-MUI also does not use maslahah as a legal consideration in a free or liberal way. Rather, it returns maslahah in consideration of the method, so that it is permissible to use the bayâ€™ al-'inÄn contract only in a forced state (á¸arurah).